Echogenic, Ultrasound-Sensitive Chitosan Nanodroplets for Spatiotemporally Controlled DKK-2 Gene Delivery to Prostate Cancer Cells - Liu X (Dove Medical Press, 2021)
Xinxin Liu, Dandan Shi, Lu Guo, Xiaoying Zhou, Mengmeng Shang, Xiao Sun, Dong Meng, Yading Zhao, Jie Li Department of Ultrasound, Qilu Hospital of Shandong University, Jinan, People’s Republic of ChinaCorrespondence: Jie LiDepartment of Ultrasound, Qilu Hospital of Shandong University, Wenhua Western Road, Jinan 107#, People’s Republic of ChinaTel/Fax +86-531-82166101Email jieli301@163.comPurpose: To synthesize echogenic chitosan/perﬂuorohexane nanodroplets (CNDs) for DKK-2 gene delivering in a spatiotemporally controlled manner in vitro.Methods: The characteristics, contrast-enhanced ultrasound imaging, DNA binding and DNase protection capacity, DKK-2 gene transfection and effects on LNCaP cells of these CNDs were investigated.Results: The obtained CNDs showed positive surface charges and could attract the genetic cargo with negative surface charges to form nanocomplexes. Agarose gel electrophoresis confirmed binding of the CNDs and pDNA. DKK-2 pDNA-loaded CNDs, in combination with ultrasound, ruptured and released DKK-2 pDNA, entering LNCaP cells through nano-scale pores in the cell membrane, which further reduced the proliferation of LNCaP cells.Conclusion: These stable and safe CNDs may be a promising choice to achieve efficient ultrasound-mediated gene delivery to specific tissues in a spatiotemporally controlled manner.Keywords: nanodroplets, chitosan, DKK-2, ultrasonic gene transfer, prostate cancer